The Relationship Between Stakeholders and Corporate Reputation in the Education Industry - Russel Wei Wern (Tecno Scientifica Publishing, 2021)
This paper analyses the relationship between Stakeholders and Corporate Reputation in the Education Industry. Through the qualitative research methodology of surveys, responses from stakeholders of different levels in the education industry has been analysed. More specifically, the areas of corporate reputation analysed were stakeholders’ management, stakeholder communication, Integrating Stakeholder Management and Communication to become Stakeholder Engagement, corporate reputation, image and identity and reputation and trust. From the analysed survey, it was found that engagement through actions of the organisations towards its stakeholders creates value and trust as two-way symmetrical communication for greater decision making.